Soil biological properties as influenced by phospho-enriched compost and fertility levels in maize (Zea mays) - DOODHAWAL, KIRAN; MEENA, R H; JAT, GAJANAND; JAIN, DEVENDRA; CHOUDHARY, R S; CHOUDHARY, ROSHAN; SHARMA, JITENDRA KUMAR; MEENA, MANISHA; YADAV, S K (The Indian Journal of Agricultural Sciences, 2021)
The present investigation was carried out to evaluate the impacts of phospho-enriched compost and fertility levels on soil biological properties in Typic Haplustepts soil of Sub-humid Southern Plain and Aravalli Hills Region in Rajasthan. The experiment was undertaken during kharif 2018 and 2019 at Instructional Farm (Agronomy), Rajasthan College of Agriculture, Udaipur (Rajasthan). The treatments comprised four levels of phospho-enriched compost (PEC), i.e. control, PEC @ 2.0, 4.0 and 6.0 t/ha and four levels of fertility (kg/ha) i.e. control, 50% RDF + foliar spray of Zn @ 0.5%, 75% RDF + foliar spray of Zn @ 0.5% and 100% RDF + foliar spray of Zn @ 0.5%, respectively. The experiment was laid out in a factorial randomized block design with three replications. Significant improvement in different soil biological properties, i.e. alkaline phosphate activity, dehydrogenase activity and soil microbial biomass carbon was observed with increasing levels of phospho-enriched compost and fertility up to 6 t/ ha and 100% RDF + foliar spray of Zn @ 0.5%, respectively after harvest of the maize (Zea mays L.) crop during both the years as well as in pooled analysis. In case of fertility levels, however, the microbial populations in soil after harvest of crop increase was significant up to 75% RDF + foliar spray of Zn @ 0.5% which was found statistically at par with 100% RDF + foliar spray of Zn @ 0.5%. The application of phospho-enriched compost @ 6 t/ha and 100% RDF + foliar spray of Zn @ 0.5% along with the recommended dose of fertilizer results in significantly higher biological properties of soil under Typic Haplustepts.